Knowledge, Attitude, and Practice of Antibiotic Use among Medical Students in the College of Medicine, National University, Oman - Al-rudaini, Mazin; Sanam Anwar; Hala Al Sawaii; Ranim Al Balushi; Taqwa Al Bahrani; Thuraiya Al Kindi; Yaqeen Al Jabri; Zainab ALHabsi (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To assess the knowledge, attitude, and practice toward antibiotic use among medical students at the College of Medicine, Oman. METHODOLOGY: A cross-sectional study was conducted at the College of Medicine, where both pre-medical and medical students participated in data collection from November 2023 to January 2024. A structured pretested questionnaire was used to collect data from all students. SPSS version 20 was used for data analysis. Independent variables were presented as frequencies and percentages, while the total knowledge score was presented as the mean and standard deviation. The mean total knowledge score was analyzed to independent variables using a t-test. RESULTS: A total of 472 students participated in this study, with most (74.2%) having no prior training on antibiotic use. Students with prior training on antibiotic use had better knowledge (81.5±18.4) than those without it (62.1±25). Most students (87.7%) recognised that improper antibiotic use could lead to antibiotic resistance in the future, and the mean total knowledge score was 67.14 ± 24.9. A high percentage of students reported stopping the antibiotics once symptoms subsided (56.6%). CONCLUSION: Medical students’ knowledge of proper antibiotic use was generally good. Knowledge of students with previous training courses and those from clinical years was higher. There was a very significant association between poor knowledge and bad antibiotic practices, like using antibiotics for self-medication and stopping antibiotics when symptoms subside.